IMPLEMENTASI PENGGUNAAN KOMPUTER SEBAGAI MEDIA DALAM MENINGKATKAN AKREDITASI DAN MUTU PENDIDIKAN DI SMP AMIR ISLAM PANYULA KABUPATEN BONE - Kasmawati, Kasmawati (Jurnal Ilmiah Mandala Education (JIME), 2021)
This study aims to determine the implementation of planning systems can improve the quality of education in SMP Amir Islam Panyula, Bone Regency. The type of research used in this research is qualitative with a descriptive approach. The subjects of this study were the principal, vice principal and teachers of SMP Amir Islam Panyula, Bone Regency, totaling 4 people with a distribution of 1 principal, 1 deputy principal and 1 teacher. The research instrument used in the form of observation and interviews. The data obtained were then analyzed by presenting the data for conclusion drawing and verification (conclusion drawing). Based on the results of the study indicate that the principal's efforts in improving the quality of education in SMP Darussalam are seen in the input, process, and output indicators. The principal's efforts to improve the quality of education related to input indicators are to prepare professional educators; either through coaching; discussions and meetings; academic seminars; include training, workshops; and education and training, perfecting student recruitment strategies through promotions. The efforts of the head of SMP Amir Islam Panyula, Bone Regency in improving the quality of education in relation to process indicators are planning for accreditation with a computer media system, creating a safe learning environment; cozy; and stimulate in learning, make programs according to the needs of students extracurricular activities, provide motivation to learn; both giving rewards and punishments to teachers and students. The efforts of the head of SMP Amir Islam Panyula, Bone Regency, in improving the quality of education in relation to output indicators, are trying to excel in academic and non-academic.